Improving Health Outcomes for the Poor in Uganda : Current Status and Implications for Health Sector Development - World Bank (Washington, DC, 2013)
This study shows that Uganda has similar or somewhat better health indicators than other African countries with a similar income level. However further effort is needed to address inequality in health outcomes and in the health system. Overall recommendations arising from this report, which are discussed in detail in Chapter 8, center on five areas: (a) prioritizing interventions that affect infant and maternal mortality, (b) improving health promotion and disease prevention practices at the family and community level through community mobilization and inter-sectoral collaboration, (c) mobilizing funds for the health sector including strategies that encourage risk polling mechanisms; (d) focusing on human resources and collaboration with the private sector to improve health service delivery, and (e) improving accountability through improving information systems and supervision.